Antiquities of the southern Indians, particularly of the Georgia tribes - Jones, Charles C., Jr. (Charles Colcock), 1831-1893 (Classics in southeastern archaeology., 1999)
Long a classic of southeastern archaeology, Charles Jones's Antiquities of the Southern Indians was a groundbreaking work that linked historic tribes with prehistoric "antiquities." Published in 1873, it predated the work of Cyrus Thomas and Clarence Moore and remains a rich resource for modern scholars. Jones was a pioneer of archaeology who not only excavated important sites but also related his findings to other sites, to contemporary Indians, and to artifacts from other areas. His work covers all of the southeastern states, from Virginia to Louisiana, and is noted for its insights into the De Soto expedition and the history of the Creek Indians. Best known for refuting the popular myth of the Mound Builders, Jones proposed a connection between living Native Americans of the 1800s and the prehistoric peoples who had created the Southeast's large earthen mounds. His early research and culture comparisons led to the eventual demise of the Mound Builder myth. -- Provided by publisher